PowerShell and Python Together Targeting Digital Investigations - Hosmer, Chet (Berkeley, CA : Apress Imprint: Apress, 2019)
Bring together the Python programming language and Microsoft's PowerShell to address digital investigations and create state-of-the-art solutions for administrators, IT personnel, cyber response teams, and forensic investigators. You will learn how to join PowerShell's robust set of commands and access to the internals of both the MS Windows desktop and enterprise devices and Python's rich scripting environment
1
Keywords: Protection de l'information (Informatique); Python (Langage de programmation)